The “I” as Implicated Subject: Performative Confession in Rian Malan’s My Traitor’s Heart - Moon, Jihie (Humanities (Basel), 2024)
Confessional forms of autobiographical writing have predominated in post-apartheid South African literary studies. This paper discusses Rian Malan’s My Traitor’s Heart, published in 1990 during drastic social and political changes in South Africa’s transition to democracy. It was one of the first and most prominent examples of this genre. Focusing on Malan’s perspective as a white Afrikaner and an “implicated subject”, this study explored how his confessional account grappled with the existential dilemma of post-apartheid Afrikaner identity. Malan simultaneously affirmed his Afrikaner identity to confront his implication in apartheid and sought to establish a legitimate place for this identity within the new multicultural society. Through a close reading of Malan’s strategic performance, this paper argues that his work offers a means of reimagining the collective self in a new community and understanding historical injustices from a multidimensional perspective. Ultimately, My Traitor’s Heart contributes to the post-apartheid project of envisioning a more inclusive psychological and topographical construction of individual and collective identity, with the implicated subject as its centre.